Studi Konversi Pati Ubi Kayu (Cassava Starch) menjadi Glukosa secara Enzimatik - gita indah budiarti (Universitas Ahmad Dahlan, 2016)
Cassava starch has potential as raw material for production glucose and fructose in Indonesia. Glucose of cassava starch can be used as substitute of cane sugar and synthetic sweetener. Glucose of starch production process includes acid hydrolysis and enzymatic hydrolysis. Enzymatic hydrolysis is usually used because non-corrosive, low reaction temperatures and no contaminate product of hydrolysis. Therefore, the purpose ofÂ this paper is to provide existing knowledge of steps process, factors influencing, kind of enzyme and sugar product from enzymatic hydrolisis of cassava starch .